2011
DOI: 10.1007/s12192-010-0224-8
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins as biomarkers for the rapid detection of brain and spinal cord ischemia: a review and comparison to other methods of detection in thoracic aneurysm repair

Abstract: The heat shock proteins (HSPs) are members of highly conserved families of molecular chaperones that have multiple roles in vivo. We discuss the HSPs in general, and Hsp70 and Hsp27 in particular, and their rapid induction by severe stress in the context of tissue and organ expression in physiology and disease. We describe the current state of knowledge of the relationship and interactions between extra-and intracellular HSPs and describe mechanisms and significance of extracellular expression of HSPs. We focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 158 publications
0
55
0
Order By: Relevance
“…Elevated HSP70 in the serum or tissues appears to be a nonspecific indicator of organ ischemia or dysfunction. HSP70 is valuable as an immediate, secreted biomarker of critical, ongoing cellular ischemia in brain and spinal cord ischemia models (Hecker and McGarvey 2011). Our work group demonstrated previously that serum HSP70 levels are associated with disease severity in chronic heart failure patients, but did not find correlation between HSP70 and CRP, TNF-alpha or IL-6 (Gombos et al 2008).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…Elevated HSP70 in the serum or tissues appears to be a nonspecific indicator of organ ischemia or dysfunction. HSP70 is valuable as an immediate, secreted biomarker of critical, ongoing cellular ischemia in brain and spinal cord ischemia models (Hecker and McGarvey 2011). Our work group demonstrated previously that serum HSP70 levels are associated with disease severity in chronic heart failure patients, but did not find correlation between HSP70 and CRP, TNF-alpha or IL-6 (Gombos et al 2008).…”
Section: Introductionmentioning
confidence: 78%
“…The possible role of HSP70 as a biomarker of cellular damage in ischemia of the brain and spinal cord has been reviewed recently (Hecker and McGarvey 2011). HSP70 is particularly valuable as an immediate, secreted biomarker in cellular ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To test this idea, we primarily focus on brain tissues because neuronal cells abundantly express HSPs and are highly vulnerable to a variety of cellular stresses, such as hypoxia/anoxia as well as disturbances in energy homeostasis (Hecker and McGarvey, 2011;Stetler et al, 2010). Furthermore, brain tissues also have a practical advantage in postmortem RNA profiling; it has been demonstrated that postmortem gene transcripts in brain tissues are relatively stable and intact with longer PMI, and are thus suitable for extraction and quantitative analyses of RNA (Heinrich et al, 2007a;2007b;Leonard et al, 1993;Popova et al, 2008).…”
Section: Introductionmentioning
confidence: 99%